1964
DOI: 10.1083/jcb.20.2.249
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Formation of Cilia and Filaments in Rumen Protozoa

Abstract: The large oligotrich rumen protozoa Diplodiniurn ecaudatum and Ophryoscolex caudatus have been studied by electron microscopy during interphase and division. The structure of mature cilia is contrasted with that seen during their formation particularly in a tuft where development lags and is arrested. Here the shaft is only a few micra long and is composed of filaments that have circular cross-sections not in the typical circular arrangement. In their diameter and appearance the filaments are similar to filame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0
2

Year Published

1966
1966
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(79 citation statements)
references
References 30 publications
5
72
0
2
Order By: Relevance
“…The paired centrioles of most animal cells undergo replication at a specific time during division and apparently play a role in the architecture of the spindle (Amano, 1957;Inout, 1964;Roth and Shigenaka, 1964;Krishan and Buck, 1965;Murray et al, 1965).…”
Section: Introductionmentioning
confidence: 99%
“…The paired centrioles of most animal cells undergo replication at a specific time during division and apparently play a role in the architecture of the spindle (Amano, 1957;Inout, 1964;Roth and Shigenaka, 1964;Krishan and Buck, 1965;Murray et al, 1965).…”
Section: Introductionmentioning
confidence: 99%
“…Satir (1963Satir ( , 1965 reasoned that, after such a quick fixation, examining the fine structure of the axoneme of cilia captured in different positions would show how contraction occurred. What to examine was not obvious, but then Roth and Shigenaka (1964) showed that, in certain axonemes, the tips did not retain the 9+2 pattern; some of the doublets became singlets. One could imagine that if some of the doublets contracted to bend the cilium in-say-the direction of the effective stroke, the doublets that contracted would become singlets and would disappear from the tips before the doublets on the opposite side (that of the recovery stroke).…”
mentioning
confidence: 99%
“…In Diplodium (Roth and Shigenaka 1964) they were found on the inside as well as on the outside of the macronucleus during division. In the present species, they are found only in the cytoplasm outside the nuclear envelope.…”
Section: Microtubulesmentioning
confidence: 97%
“…Microtubules were observed in the stage of the macronuclear division in several species of ciliate (Roth and Minick 1961, Roth and Shigenaka 1964, Raikov 1965, Carasso and Favard 1965, Suganuma and Inaba 1967.…”
Section: Microtubulesmentioning
confidence: 99%